THE IMPORTANCE OF FOREIGN EXPERIENCE IN IMPROVING THE HUMAN RESOURCE MANAGEMENT SYSTEM (ON THE EXAMPLE OF THE CUSTOMS SERVICE) (World Economics and Finance Bulletin, 2026)
THIS
Keywords: Human resources